Posterior wall isolation using the cryoballoon ablation in patients with persistent and long-standing persistent atrial fibrillation - A. S. Omelyanenko; T. M. Uskach; T. I. Mavludov; A. R. Nasibullina; D. F. Khaziakhmetov; D. I. Cherkashin; D. F. Ardus; O. V. Sapelnikov (Евразийский Кардиологический Журнал, 2025)
Aim. To evaluate the efficacy and safety of posterior wall isolation using the cryoballoon ablation in patients with persistent and long-standing persistent forms of atrial fibrillation in comparison with pulmonary vein antrum cryoballoon isolation.Methods. One hundred seventeen (n=117) patients with persistent (n=73) and long-standing persistent (n=44) atrial fibrillation, median left ventricular ejection fraction was 58,0% [54,0; 60,0]. The median size of the left atrial was 4,2 cm [4,00; 4,60]. A comparative analysis of the results of cryoballoon isolation supplemented with isolation of the posterior wall of the left atrium – group A (61 patients) and classic cryoballoon pulmonary vein antrum cryoballoon isolation – group B (56 patients) was performed.Results. In one-year follow-up the efficacy of cryoballoon isolation supplemented with isolation of the posterior wall of the left atrium was significantly higher – 73,8% (n=45) than in cryoballoon pulmonary vein isolation – 67,9% (n=38) (p=0,030). There were no statistically significant differences in complication rates between the groups. No life-threatening complications were recorded during this study.Conclusion. Both methods showed comparable safe results. Isolation of the posterior wall using cryoballoon in addition to pulmonary vein isolation is a more effective method of catheter treatment of persistent and long-persistent forms of atrial fibrillation in comparison with classic cryoballoon isolation of the atrial fibrillation.